First record of leaf cuttings under natural conditions in Phyllagathis (Melastomataceae) - Kiew, Ruth; Mohamed, Latipah (Malaysian Nature Society, 1981)
Development of leaf cuttings under natural conditions f is recorded for the first time in Phyllagathis griffithii King and P. rotundifolia BI. (Melastomataceae). The rarity of leaf cuttings in flowering plants and the relative importance of vegetative and sexual reproduction in the undergrowth of the tropical rainforest are discussed.